Mexican American Birthweight and Child Overweight: Unraveling a Possible Early Lifecourse Health Transition - Hamilton, Erin R. (2011)
Mexican American children have a weight distribution that categorizes them as relatively healthy at birth but relatively unhealthy by age 3. This early lifecourse transition in health based on weight raises the question of whether Mexican American children “outgrow” the epidemiologic paradox of favorable birth outcomes despite social disadvantage or whether their birthweight distribution places them on trajectory for overweight in childhood. We address this question using newly available 9-year follow-up data from the Fragile Families and Child Wellbeing birth cohort study linked to prenatal medical records. We systematically investigate the roles of birthweight, pre-natal factors, and childhood factors in explaining racial/ethnic differences in childhood overweight. Our main finding is that Mexican American children do outgrow the paradox: their rates of childhood overweight are higher than expected given their birthweight distribution. Observed pre-natal and childhood factors do not explain the elevated rates of overweight among Mexican American children.